The influence of harmonic current on distribution transformer losses - Emi Zurima Ismail (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2014)
This thesis is all about explaining the research project which entitled the influence of harmonic current on distribution transformer losses. The harmonic current has been investigated and analyzed intensely.